2021
DOI: 10.1051/parasite/2021073
|View full text |Cite
|
Sign up to set email alerts
|

Soil contamination by Echinococcus multilocularis in rural and urban vegetable gardens in relation to fox, cat and dog faecal deposits

Abstract: Echinococcus multilocularis eggs are deposited on the ground with the faeces of the carnivore definitive hosts. A reliable assessment of the spatial distribution of E. multilocularis eggs in environments used by humans is crucial for the prevention of alveolar echinococcosis (AE). This study was conducted in 192 rural and 71 urban vegetable gardens in AE endemic areas of north-eastern France. Its objective was to explore the relationship between the spatial distribution of E. multilocularis estimated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…Vegetables from contaminated environments should be washed or cooked before being consumed, to avoid the risk of ingesting viable Toxocara eggs, while hand hygiene following contact with soil should also be observed. It should also be noted that absence of visible faeces does not rule out historical contamination and persistent infection risk from gardens, as confirmed for the zoonotic tapeworm of foxes and dogs, Echinococcus multilocularis ( Da Silva et al, 2021 ), while cats tend to bury their faeces, concealing signs of elevated Toxocara hazard ( Maciag et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables from contaminated environments should be washed or cooked before being consumed, to avoid the risk of ingesting viable Toxocara eggs, while hand hygiene following contact with soil should also be observed. It should also be noted that absence of visible faeces does not rule out historical contamination and persistent infection risk from gardens, as confirmed for the zoonotic tapeworm of foxes and dogs, Echinococcus multilocularis ( Da Silva et al, 2021 ), while cats tend to bury their faeces, concealing signs of elevated Toxocara hazard ( Maciag et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, praziquantel should be prescribed to all cats with hepatobiliary diseases in Thailand. Echinococcosis is another possible cause of hepatic cysts in cats [ 29 ]. To the authors’ knowledge, echinococcosis in cats has never been reported in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“… Measurement of the shortest distance from murid rodents to feces of red fox. ), because the area around feces was contaminated [ 3 ], thereby rodents where were near the feces had the possibility of echinococcus infection. Data on rodents within 30 cm of the feces were used, because rodents far from the feces would be difficult to contact contaminated soil.…”
Section: Methodsmentioning
confidence: 99%